The Detailed Description of Construction Waste in Low-Cost Housing Projects in Indonesia - Nurlaelah Nurlaelah; Arman Jayady (Logistic and Operation Management Research (LOMR), 2022)
Developers construct low-cost housing specifically for the low-income demographic. While the number of people interested in this sort of home is growing in Indonesia, in practice, there is sometimes a delay in the development process due to waste. The goal of this research is to identify and describe the waste that occurs during the construction of low-cost dwellings. Field observations and interviews with 17 contractors working on four low-cost housing projects were used to gather data. The findings of the analysis demonstrate that various wastes arise throughout the construction process' flow, including waste Overproduction, Inventory, Defect, Motion, Transportation, Processing, and Waiting in each job, all of which stymie the development process. This study was not conducted at the level of the developer or material supplier, but rather at the project site, specifically on every job in the process of constructing a consumer's home. This study uses seven forms of waste that exist in a succession of manufacturing processes, namely Overproduction, Inventory, Defect, Motion, Transportation, Processing, and Waiting, which are rarely employed in construction projects.